Analisis Efektivitas Layanan Bimbingan dan Konseling dalam Membentuk Karakter Siswa di SMPN 2 Telukjambe - Tiara Khaerani Hasibuan; Yandi Maulana; Zulfa Telian Ristamala; Siti Atiqoh; Nur Aini Farida (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
This research is motivated by the increasing number of character issues in students within the school environment, such as low discipline, lack of responsibility, and behavior that does not reflect social values. This situation highlights the importance of Guidance and Counseling (BK) services in supporting more targeted and sustainable character development in students. This study aims to describe the effectiveness of BK services in shaping student character at SMPN 2 Telukjambe. The study used a qualitative descriptive approach, with one BK teacher and two ninth-grade students selected purposively because they had participated in BK services. Data were obtained through observation and semi-structured interviews, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that BK services are implemented in a structured manner through classical guidance, individual counseling, and character development activities integrated with religious programs. Collaboration between BK teachers, Islamic Religious Education teachers, homeroom teachers, and parents is a key supporting factor in shaping student character. However, challenges remain in detecting student problems that are not directly visible, necessitating increased counselor sensitivity and strengthening early detection strategies.